Implementasi Sistem Pendukung Keputusan Penilaian Soft Skill Guru Berbasis Web Menggunakan Metode Weight Product - Rizky Pratama; Ruri Ashari Dalimunthe; Endra Saputra (Building of Informatics, Technology and Science (BITS), 2022)
MTs Nurul Iman Simpang Empat is a private school institution located in Asahan Regency which has 32 madrasa teachers. This madrasa has quite complete facilities and is supported by technology facilities and a fairly complete information system. MTs Nurul Iman Simpang Empat is also included in the pilot MTs for other schools, because MTs Nurul Iman Simpang Empat has many achievements in various fields. Every year, the Principal holds a Teacher Soft Skill Assessment to improve the quality of education in Madrasahs. This study aims to determine the soft skill system for teachers in the school so that the performance of each teacher is obtained. Obstacles from Teacher Performance Assessment at MTs Nurul Iman Simpang Empat are still subjective in assessment based on assessment because there is no system of assessment used in Teacher Soft Skill Assessment. In the decision support system there are several methods that can be used in solving a problem. The research method used is a qualitative method with data collection techniques using interviews and literature studies. The program design method uses a weight product with the PHP programming language and MySQL as the database